Christianity and power politics today: Christian realism and contemporary political dilemmas - Patterson, Eric (Palgrave Macmillan, 2008)
This volume aims to reconstruct and debate a contemporary Christian realist framework, while also applying such a perspective to the issues of contemporary politics such as the Bush Doctrine, the laws of war, democracy and democratization, U.S. participation in international institutions, and apocalyptic terrorism